Strategic Thinking: a Resource to Generate Value and Cross the Valley of Death of SMEs - Casanueva-Yánez, Galvarino; Torres-Vásquez, Jorge; Linares-Vizcarra, Mitzi; Lukich-Valdivia, Milena; Montero-Zuñiga, Evelyn; Pérez-Vargas, Reina; Torres-Calvimonte, Claudia; Rengifo-Lozano, Raúl (Journal of Ecohumanism, 2024)
The most challenging period for a company is the first three years following its inception, a period often referred to as the "valley of death." This article examines the factors contributing to the high mortality rate of small and medium-sized enterprises (SMEs) in the town of Melipilla, Chile, and presents potential strategies for reducing or preventing this mortality. The study employs an exploratory-descriptive approach, utilizing a qualitative methodology and a cross-sectional sample size collected through convenience sampling and semi-structured interviews. Upon analysis of the aforementioned data, it becomes evident that contemporary SMEs have more convenient access to capital, technology, information, and financing. These resources, which were once considered distinctive and crucial for competitive advantage, are no longer as pivotal in generating value. Conversely, the findings highlight the pivotal role of human resources and their strategic management in developing distinctive competencies, which are essential for SMEs to create value and ensure long-term sustainability.